A Prospective Comparative Study of Health Inequalities and the Epidemiology of Stroke in French Guiana and Dijon, France - Devi Rita Rochemont; Emmanuelle Mimeau; Caroline Misslin; Martine Papaix-Puech; Bertrand de Toffol; Nadia Sabbah; Emmanuel Delmas; Yannick Bejot; Isabelle Fournel; Isabelle Fournel; Mathieu Nacher; Mathieu Nacher (Frontiers Media S.A., 2022)
BackgroundIn French Guiana poverty is widespread and specialized care is lacking. We aimed to compare strokes between precarious and non-precarious patients within French Guiana and to compare the epidemiology of ischemic strokes and their outcomes between French Guiana and mainland France.MethodsA multicenter prospective cohort examined the influence of social inequalities on stroke characteristics. Consecutive patients aged > 18 years admitted for an acute ischemic stroke, confirmed by neuroimaging were eligible. Exclusion criteria were a history of symptomatic stroke, presence of other short-term life-threatening diseases and inability to contact patients by telephone during follow-up. Social deprivation was measured using the EPICES score, which is based on a multidimensional questionnaire.ResultsOverall, 652 patients with ischemic stroke were included. The patients in French Guiana were 7 years younger, were more frequently male, of sub-Saharan ancestry, they had a low level of education, and were more often precarious (67.7%) than the patients included in Dijon (39.2%). The origin of the ischemic stroke was predominantly lacunar for patients included in French Guiana and cardioembolic for patients included in Dijon, with greater severity for patients included in Dijon. The proportion of patients with known pre-stroke hypertension, diabetes, or a history of Transient Ischemic Accident was greater in French Guiana than in Dijon. In contrast, hypercholesterolemia, atrial fibrillation, and history of Myocardial Infarction were more frequently found in patients included in Dijon than in patients included in French Guiana. Fibrinolysis was less frequent in French Guiana than in Dijon, 24% of patients arriving early enough receiving thrombolysis in French Guiana vs. 45% in Dijon, P < 0.0001. However, after adjustment for patient characteristics, the effect of the center on the use of fibrinolysis disappeared. When comparing precarious and non-precarious patients within French Guiana, the main difference was the younger age and the lower mortality of precarious patients-notably immigrants.ConclusionPrecariousness was widespread in French Guiana. Within French Guiana, despite a younger age among foreigners than French patients, the risk factors, mechanisms, and outcomes were homogenous across socioeconomic strata. The observed differences between the two contrasted French territories suggested that, beyond health inequalities, the epidemiology of cardiovascular risk factors may differ between French Guiana and mainland France.